An overview of quality assessment methods of video transmission over wireless networks - Chaari Ep Bouaziz, Hekma; Chaari, Hekma; Mnif, Kais; Kamoun, Lotfi (Proceedings of the Mediterranean Electrotechnical Conference - MELECON, 2012)
Video streaming presents the professional communicator with a whole new way to deliver information, messages, and entertainment. As third generation wireless networks are deployed, they offer the possibility to view video from mobile terminals. Video transmission is very sensitive to bit errors especially in wireless transmission (packet loss, end to end delay, etc.), the encoder used for transmission affect also the quality of video, that's why it is important to search a method that monitor and adjust the quality of a video sequence. In this paper, a survey of existing quality assessment methods monitor methods is presented. Indeed, three methods will be detailed: objective metrics, subjective evaluation and pseudo-subjective assessment. The discussion includes the advantages and disadvantages of each method. © 2012 IEEE.
Created from Fastlane, Scopus look-up
Keywords: Objective metrics; PSQA; QoS; QoU; subjective evaluation